Estanislao zuleta meets sigmund freud about art and literature (1992)
Zuleta draws on philosopher's arguments, and specially Nietzsche's, and clings on to Freud himself, to reject any kind of rupture between psychoanalysis (and science) and art,  literature or philosophy. Hesees works of art in Freud's analyses, while every work of art is in itself a job of philosophical and scientific interpretation. Ultimately, thinking is a job of psychoanalysis; a way of resolving one's own drama.